Science Process Skills Profile of Madrasah Students in Supporting the Quality of Islamic Education - Suprihatin Suprihatin; Rahmi Susanti; Ermayanti Ermayanti (Yayasan Letiges Konsultan Sosial, 2026)
Science process skills (SPS) are essential competencies in science learning that support students' scientific thinking and inquiry abilities. However, empirical evidence regarding the SPS profiles of madrasah students as a basis for improving science learning within the context of Islamic education remains limited. This study aimed to analyze the science process skills profiles of tenth-grade students at State Islamic Senior High School 3 Palembang based on six basic science process skill indicators and to examine differences according to gender. A quantitative descriptive approach was employed involving 230 tenth-grade students selected through total sampling. Data were collected using the Basic Science Process Skills (BAPS) test and analyzed using descriptive statistics and an independent-samples t-test at a significance level of 0.05. The results showed that the observation, communication, and classification indicators were categorized as high, whereas measurement and drawing conclusions were categorized as moderate. Prediction achieved the highest score in both gender groups. Although female students obtained a higher average SPS score (67%) than male students (63%), the difference was not statistically significant (p = 0.337 > 0.05). This study was limited to a single madrasah, and therefore the findings cannot be generalized to other Islamic educational settings. Nevertheless, the findings provide an empirical basis for teachers to design inquiry-oriented science instruction that strengthens students' science process skills and contributes to the improvement of science learning in Islamic educational institutions.